Berberine alleviates AGEs-induced ferroptosis by activating NRF2 in the skin of diabetic mice - Chunjie Jiang; Guojuan Lao; Jianmin Ran; Jianmin Ran; Ping Zhu; Ping Zhu (Experimental Biology and Medicine)
Advanced glycation end products (AGEs) have adverse effects on the development of diabetic complications. Berberine (BBR), a natural alkaloid, has demonstrated its ability to promote the delayed healing of skin wounds. However, the impact of BBR on AGEs-induced ferroptosis in skin cells and the underlying molecular mechanisms remains unexplored. This study investigated the involvement of ferroptosis in AGEs-induced keratinocyte death, and the impact of BBR on ferroptosis in a db/db mouse model with long-term hyperglycemia was elucidated. A remarkable reduction in cell viability was observed along with increased malondialdehyde (MDA) production in AGEs-induced HaCaT cells. Intracellular reactive oxygen species (ROS) and iron levels were elevated in cells exposed to AGEs. Meanwhile, the protein expression of glutathione peroxidase 4 (GPX4) and ferritin light chain (FTL) was significantly decreased in AGEs-treated cells. However, pretreatment with BBR markedly protected cell viability and inhibited MDA levels, attenuating the intracellular ROS and iron levels and increased expression of GPX4 and FTL in vitro. Significantly diminished antiferroptotic effects of BBR on AGEs-treated keratinocytes were observed upon the knockdown of the nuclear factor E2–related factor 2 (NRF2) gene. In vivo, GPX4, FTL, and FTH expression in the epidermis of diabetic mice was significantly reduced, accompanied by enhanced lipid peroxidation. Treatment with BBR effectively rescued lipid peroxidation accumulation and upregulated GPX4, FTL, FTH, and NRF2 levels in diabetic skin. Collectively, the findings indicate that ferroptosis may play a significant role in AGEs-induced keratinocyte death. BBR protects diabetic keratinocytes against ferroptosis, partly by activating NRF2.